2008
DOI: 10.3390/md6040607
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities of Hydrolysates of Arca Subcrenata Prepared with Three Proteases

Abstract: Abstract:In order to get products with antioxidant activity from Arca subcrenata Lischke, the optimal hydrolase and hydrolysis conditions were investigated in the paper. Three proteases (neutrase, alcalase and papain) were applied to hydrolyze the homogenate of A. subcrenata. An orthogonal design was used to optimize hydrolysis conditions, and the pH-stat methods was used to determine the degree of hydrolysis. Viewed from the angle of reducing power, such as scavenging activities against α,α-diphenyl-β-picrylh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 28 publications
4
28
2
Order By: Relevance
“…Residual cake hydrolysate showed a concentration-dependent increase of antioxidant activity for concentrations up to 0.9 g L −1 of protein. This linear behavior has been observed by other researchers for different hydrolysates (Song et al 2008;Balti et al 2011). The IC 50 value was 0.91±0.01 g L −1 of protein and was lower than that reported by Song et al (2008) for Arca subcrenata hydrolysate (6.23 g L −1 of protein).…”
Section: Antioxidant Capacitysupporting
confidence: 87%
“…Residual cake hydrolysate showed a concentration-dependent increase of antioxidant activity for concentrations up to 0.9 g L −1 of protein. This linear behavior has been observed by other researchers for different hydrolysates (Song et al 2008;Balti et al 2011). The IC 50 value was 0.91±0.01 g L −1 of protein and was lower than that reported by Song et al (2008) for Arca subcrenata hydrolysate (6.23 g L −1 of protein).…”
Section: Antioxidant Capacitysupporting
confidence: 87%
“…Non-hydrolyzed gelatin was negligible in reducing FRAP reagent. In Arca subcrenata case, the neutrase hydrolysate displayed the most reductive ability and alcalase was the second best (Song et al 2008). Alemán et al (2011b) reported that the highest FRAP values occurred in squid skin gelatin hydrolyzed with alcalase and in tuna skin gelatin hydrolyzed with trypsin.…”
Section: Antioxidant Activities Of Each Hydrolysatementioning
confidence: 99%
“…Gelatin was extracted from washed fish skins added with distilled water (1:2w/v) by heating at 60°C for 1.5 h. The resulting gelatin solution was then filtered through double layer cheese cloth and lyophilized. The freeze-dried gelatin was dissolved in 0.1 M sodium phosphate buffer and hydrolyzed separately by six different protease enzymes under the previously reported conditions: alcalase (pH 7.0, 50°C), bromelain (pH 7.0, 55°C), flavourzyme (pH 7.0, 50°C), neutrase (pH 8.0, 50°C), papain (pH 6.0, 37°C) and trypsin (pH 8.0, 37°C) (Song et al 2008;Zhao et al 2009;Alemán et al 2011a;Li-Chan et al 2012). The ratio for the enzyme:substrate was 1:100 (w/w).…”
Section: Gelatin Extraction and Hydrolysismentioning
confidence: 99%
“…Antioxidative compounds have been shown to scavenge ABTS radicals at higher level compared to DPPH radicals (Sachindra and Bhaskar 2008). Many antioxidant peptide sequence identified have been reported to contain hydrophobic amino acid residues, especially valine or leucine, at the N-terminus of peptides apart from proline, histidine and tyrosine in the sequence (Song et al 2008). Previous studies by our group have indicated (Bhaskar et al 2007a;Amit et al 2009a, b, c), that both AH and LFH have all these amino acids, except histidine, in considerably higher concentrations.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…In addition, The protein hydrolysates obtained from wastes/by-products of animal and fish processing industry are reported to exhibit bioactivities like antioxidative (Wu et al 2004, Sachindra and, antihypertensive (Suetsuna et al 2004) and immunomodulatory properties (LeBlanc et al 2002, Tsuruki et al 2003. In recent years there is a growing interest in antioxidant properties of natural source such as protein due to the potential health hazards of certain synthetic antioxidants (Song et al 2008). During fermentation or acid silaging, TF proteins (that are rich in collagen) are hydrolysed forming a liquor and an insoluble residue.…”
Section: Introductionmentioning
confidence: 99%